Dal Bon, Bruno. 2020. La Gioia Sovrana: Nietzsche e la Musica come Filosofia. Milano: Mimesis Edizioni. - Molteni, Pietro (Current Musicology, 2023)
La Gioia Sovrana, Nietzsche e la Musica come Filosofia is a book written by the Italian conductor and philosopher Bruno Dal Bon. It demonstrates that music is one of the fundamental driving forces that moved Nietzsche in his philosophical activity.